Numerical model development to predict the behaviour of infant/neonate crash dummy restrained inside of an incubator under deceleration - Rabiee, Ali; Ghasemnejad, Hessam; Hitchins, Nicholas; Watson, James W.; Roberts, James; Khoory, Matthew (Springer, 2021)
In this paper, advanced finite element (FE) methods are developed to investigate the effect of deceleration on the crash dummy test complied with British Standard Engineering (BS EN 1789). These techniques, which are related to material modelling, joints and contacts, offer an advanced numerical model representing an infant incubator with all complex boundary conditions and design contents. It is shown that the response of an infant incubator is a function of the ratchet straps, the tension on the belts, the belt type and the distance of the belts from the edges of the incubator, which can significantly affect the experienced acceleration, by the infant. The validation process is performed against experimental studies and various case parameters such as crash dummy mass and negative acceleration impulse are discussed in detail. The developed numerical model is capable to predict the behaviour of the crash dummy and the incubator in terms of acceleration, trajectory and kinematics by less than 8% error.
Keywords: LS-DYNA; Biomechanics; Crash dummy; Incubator